STEM integration in K-12 education : status, prospects, and an agenda for research - Honey, Margaret; Pearson, Greg; Schweingruber, Heidi A. (The National Academies Press, 2014)
During the past decade, the STEM acronym has developed wide currency in U.S. education and policy circles. Leaders in business, government, and academia assert that education in the STEM subjects (science, technology, engineering, and mathematics) is vital not only to sustaining the innovation capacity of the United States but also as a foundation for successful employment, including but not limited to work in the STEM fields. Historically, U.S. K-12 STEM education has focused on the individual subjects, particularly science and mathematics. Reform efforts, including the development of learning standards and, more recently, large-scale assessments, likewise have treated the STEM subjects mostly in isolation. Education for K-12 students in STEM has received increasing attention during the past decade with calls both for greater emphasis on these fields and for improvements in the quality of curricula and instruction. In response, numerous new instructional materials, programs, and specialized schools are emerging. While most of these initiatives address one or more of the STEM subjects separately, there are increasing demands for emphasizing connections between and among the subjects. The relatively recent introduction of engineering education into some K-12 classrooms and out-of-school settings and the 2013 publication of the Next Generation of Science Standards, which explicitly connect science concepts and practices to those of engineering, have elevated the idea of integration as a potential component of STEM education. Integration in K-12 STEM Education examines current efforts to integrate the STEM disciplines in K-12 education and to develop a research agenda that if carried out could provide the data needed to inform such efforts going forward. This report identifies and characterizes existing approaches to integrated STEM education, both in formal and after- and out-of-school settings. The report reviews the evidence for the impact of integrated approaches on various student outcomes, such as greater student awareness, interest, motivation, and achievement in STEM subjects; improved college-readiness skills; and boosts in the number and quality of students who may consider a career in a STEM-related field. Finally, the report determines a set of priority research questions to advance the understanding of integrated STEM education. This book develops a framework to provide a common perspective and vocabulary for researchers, practitioners, and others to identify, discuss, and investigate specific integrated STEM initiatives within the K-12 education system of the United States. Integration in K-12 STEM Education makes recommendations for designers of integrated STEM experiences, assessment developers, and researchers to design and document effective integrated STEM education. This report will help to further their work and advocates the potential of some forms of integrated STEM education to make a positive difference in learning, interest, and other valued outcomes.